Association of composite dietary antioxidant index with prevalence of stroke: insights from NHANES 1999-2018 - Teng, Tian-Qi; Liu, Jing; Hu, Fang-Fang; Li, Qing-Qing; Hu, Zhen-Zhu; Shi, Yu (Frontiers in Immunology, 2024)
Background: There is a growing acknowledgment of the potential influence of antioxidative effects resulting from dietary decisions on the occurrence of stroke. The objective of this study was to elucidate the correlation between the composite dietary antioxidant index (CDAI) and the incidence of stroke in the general population of the United States.We gathered cross-sectional data encompassing 40,320 participants from the National Health and Nutrition Examination Survey (NHANES) spanning the years 1999 to 2018. Employing weighted multivariate logistic regression, we assessed the correlation between CDAI and stroke, while also investigating potential nonlinear relationships through restricted cubic spline (RCS) regression. Further, the intake of CDAI components were then incorporated into a predictive nomogram model, subsequently evaluated for its discriminatory prowess in stroke risk assessment using the receiver operating characteristic (ROC) curve.Results: Post-adjustment for confounding variables, we found that higher CDAI score were associated with a decreased risk of stroke, the odds ratio (OR) [95% CI] of CDAI associating with prevalence was 0.96 [0.94-0.98] (P < 0.001). Moreover, the adjusted OR [95% CI] for stroke across ascending CDAI quartiles stood at 0.